(3OQhS aj GdefgLjI GdEbJUGOjI heONd Gdi GdYdhe GdEbJUGOjI (B/s - (3gfj, CMeOs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2015)
(3ehVhY Yde GdEbJUGO(B- (3EYOGO hbjGS GdNjQGJ GdEbJUGOjI(B- (3GdfeGPL GdEbJUGOjI(B- (3GdfeGPL GdQFjSjI aj GdJMdjd GdEbJUGOj(B- (3YhGed GdfTGW GdEbJUGOj(B.s
(3GdeQGLY U(B.149s
Keywords: (3GdHMK GdYdejs; (3GdYdhe GdEbJUGOjIs